The Impact of Forensic Accounting Techniques in Detecting Creative Accounting Practices "A Survey Study of the Opinions of Certified Public Accountants in Syria" - هاشم , سجى; عفراء هلال علي ,; حيدر عبد الهادي حيدر , (Latakia University Journal - Economic and Legal Sciences Series, 2025)
The Study Tested The Impact of Forensic Accounting Techniques Used By Certified Public Accountants in Syria When Auditing Financial Companies In Detecting Creative Accounting Practices. The Survey Strategy Was Relied Upon By Distributing The Questionnaire to The Practicing Certified Public Accountants in Syria, Numbering (120) Certified Public Accountants. (97) Valid Questionnaires Were Retrieved for Analysis. The Data Were Analyzed Using The Smartpls4 Program, and The Hypotheses Were Tested Using The Multiple Regression Model. The Results Showed The Existence of an Impact of Using These Techniques in Detecting Creative Accounting Practices, and That Certified Public Accountants Rely on Them to Detect These Practices. The Results Also Showed That The Techniques of Financial Ratio Analysis and The Theory of Relative Size Have a Direct and Significant Effect. it Also Showed That There Was an Inverse and Significant Effect for The Trend Analysis Technique, While The Percentage of Explained Variance Reached (49.4%).